Parent–Child Relationship, Resilience Beliefs, Relationship Quality and Stress During the Pandemic in American Families: A Moderated Mediation Analysis - Anis Ben Brik (19239442) (2024)
The study aims to investigate factors within the double ABC‐X model to explain parents' stress during the first wave of the COVID‐19 pandemic, with a focus on adaptive resources (i.e., parent–child relationship and relationship quality) and the moderating effect of appraisal (i.e., family resilience beliefs). Drawing on a sample of 1386 American parents, this study examines the moderated mediation effects to test the conditional indirect influence of a moderating variable (i.e., family resilience beliefs) on the relationship between a predictor (i.e., stressor pile‐up) and an outcome variable (i.e., stress) through potential mediators (i.e., family satisfaction and relationship quality). The results indicate that the relationship between stressor pile‐up and parent stress was mediated by both parent–child relationship and relationship quality. In addition, the direct association between the parent–child relationship and parent stress was moderated by family resilience beliefs. However, the moderation effects of family resilience beliefs on relationship quality and stress were not supported. Family resilience beliefs moderated the indirect effect of stressor pile‐up on parent stress through the parent–child relationship, but not through relationship quality. The study emphasized the contribution of stressors and adaptive resources in understanding parental adaptation and the role of the family system in maintaining well‐being during unprecedentedly challenging times. Other Information Published in: Child & Family Social Work License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/cfs.13231